Study aimed at identifying factors with the potential to reduce the disparities in mathematics anxiety observed between 15-year-old French-speaking boys and girls in Quebec, based on an analysis of PISA data from 2003 and 2012 - Vohl, Patricia; Loye, Nathalie (Mesure et évaluation en éducation)

(untitled) (ADMEE-Canada, 2023)
A previous study (Vohl & Loye, 2023) showed that, on average, 15-year-old French-speaking Quebec girls are more anxious about mathematics than French-speaking Quebec boys across the performance continuum. The results also showed that performances in mathematics and mathematics anxiety are two negatively correlated phenomena. This paper aims to identify factors that could explain the differences in mathematics anxiety observed between girls and boys and that may have the potential to reduce the observed differences. The Pekrun’s control-value model for achievement emotions (2006) was used to verify whether differences in self-concept, intrinsic value, and utility value observed between girls and boys completely explain the differences in mathematical anxiety. The results in self-concept explain nearly 70% of the differences in mathematics anxiety observed among francophone students in Quebec.